RCTV's "Wewara" Program in Preserving Cirebon Local Wisdom - Wisnu Lanandie; Widiartha Atas Cahyadi; Aditya Pratama Rachmanto; Farida Nurfalah; Abdul Jalil Hermawan (Asian Journal of Social and Humanities, 2024)
The rapid development of technology has made it easier for humans to communicate. Communication is a process of conveying and receiving symbols that contain a meaning, whether in the form of information, thoughts, knowledge or other forms. The researcher conducted a study related to a RCTV "Wewara" Program in preserving Cirebon Local Wisdom. The purpose of this research is so that all people and readers know the importance of maintaining local wisdom and cultural communication from an area that we live in, besides that the researcher wants to know more about the process, principles, and editorial policies of the Cirebon language contained in the "wewara" news broadcast program. This research uses a qualitative descriptive research method, by conducting an interview and conducting a direct observation in the field. The results of this study show that the agenda setting agenda in RCTV's "Wewara" Program in Preserving Cirebon Local Wisdom gives birth to three stages, namely the process of problem identification (problem stream), policy determination (policy stream) and finally the political process (political stream).